Absence of differences in the learning rate of a speed–accuracy movement task between women patients with mild and major depression and healthy adult women - Mickeviciene, Dalia; Leleikiene, Aiste; Valanciene, Dovile; Vizbaraite, Daiva; Brazaitis, Marius; Skurvydas, Albertas (Human movement science, 2019)
This study tested the hypothesis that women patients with depression should perform movements more slowly and with greater variability, and their learning rate should be lower compared with age-matched healthy adult women. Three groups of adult women subjects (aged 33–37 years, women patients with mild and major depression and healthy adult women, n = 20 in each group) performed five series (20 repetitions in each series) of a speed–accuracy hand-movement task (SAT). The mean movement speed (Va) of the SAT was lower and more stable (the coefficient of variation of Va was lower) in women patients with major depression compared with those with minor depression and healthy adult women during the first series of the SAT. Only the Va and movement accuracy (path of movement, S) of the SAT varied significantly in the five learning series regardless of the subject group (healthy women subjects and women patients with minor and major depression). The intraindividual variability of reaction time, Va, maximal movement velocity to the target (tVmax), time to tVmax, and S did not change significantly in any of the groups. Our research data showed that although women patients with depression performed speed–accuracy movements more slowly, the stability of the performance of their movements and their learning rate did not differ from those of age-matched healthy adult women.